PENGARUH PELIMPAHAN WEWENANG TERHADAP EFEKTIFITAS KERJA KARYAWAN HOTEL DI KABUPATEN LEBONG - Bill Sandy; Eti Arini (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The aims of study were to describe the effectiveness of employee work, the delegation of authority that has been running and to analyze the effect of the delegation of authority with the work effectiveness of the Hotel, Lebong Regency. This research was conducted at the Hotel, Lebong Bengkulu Regency. This research is analytical research with quantitative method using cross sectional approach. The populations were all employees of the Hotel, Lebong Bengkulu Regency as many as 50 people. The analysis method used the results of descriptive analysis, bivariate analysis and simple linear regression. The results showed that the work effectiveness described on all indicators of work effectiveness showed a good category. The delegation of authority that has been running at the Hotel, Lebong Regency, shows a good category. The delegation of authority has a positive and significant effect on the work effectiveness of the Hotel, Lebong Regency. Based on linear regression analysis, the hypothesis which states that the delegation of authority has a significant effect on work effectiveness is accepted. The conclusion of the study is that the delegation of authority affects the effectiveness of employees' work. Keywords: effectiveness, hotel, work, delegation and authority Keywords: effectiveness, hotel, work, delegation and authority